Clinical impact of radioactive iodine dose selection based on the number of metastatic lymph nodes in patients with papillary thyroid carcinoma: A multicenter retrospective cohort study. (4th July 2021) - Kwon, Seong Young; Kim, Myoung Hyoun; Kong, Eunjung; Chong, Ari; Yoo, Su Woong; Jeon, Subin; Park, Soon‐Ah; Kim, Dae‐Weung; Kang, Su Hwan; Choi, Jung Eun; Ha, Jung‐Min; Jeong, Shin Young; et al.
Abstract: Objective: The aim of this study is to investigate whether the number of metastatic lymph nodes (LNs) could be used as a basis in the radioactive iodine (RAI) dose selection for patients with papillary thyroid carcinoma (PTC). Patients: A total of 595 patients with PTC who received first RAI therapy after total or near‐total thyroidectomy and had no evidence of disease in treatment response assessment were retrospectively enroled from five hospitals. The patients were classified into two subgroups based on the number of metastatic LNs (>5). The multivariate Cox‐proportional hazard model was performed to identify the significant factors for recurrence prediction in each group as well as all enroled patients. Results: Overall, 22 (3.7%) out of 595 patients had the recurrent disease during the follow‐up period. The number of metastatic LNs (>5) was only a significant factor for recurrence prediction in all enroled patients (odds ratio: 7.834, p  < .001). In the subgroup with ≤5 metastatic LNs, the presence of extrathyroidal extension was only associated with recurrence (odds ratio: 7.333, p  = .024) in multivariate analysis. RAI dose was significantly associated with recurrence rate in which the patients with high‐dose RAI (3.7 GBq or higher) had less incidence of recurrence than those with low‐dose RAI (1.11 GBq) in the subgroup with more than five metastatic LNs (odds ratio: 6.533, p  = .026). Conclusions: High‐dose RAI (≥3.7 GBq) therapy significantly lowered the recurrence rate in patients with more than five metastatic LNs. Therefore, RAI dose should be determined based on the number of metastatic LNs as well as conventional risk factors.